2014
DOI: 10.1021/ol403716t
|View full text |Cite
|
Sign up to set email alerts
|

Vicinal Difunctionalization of Alkenes: Chlorotrifluoromethylation with CF3SO2Cl by Photoredox Catalysis

Abstract: Photoredox-catalyzed vicinal chlorotrifluoromethylation of alkene is described. In the presence of Ru(Phen)3Cl2, CF3SO2Cl was used as a source for the CF3 radical and chloride ion under visible light irradiation. Various terminal and internal alkenes were transformed to their vicinal chlorotrifluoromethylated derivatives. Biologically active compounds were applied under the condition to obtain desired products, suggesting that the method could be feasible for late-stage modification in drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
92
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(96 citation statements)
references
References 30 publications
1
92
0
3
Order By: Relevance
“…[19] Also, not unexpectedly, simple thermally induced radical initiators, such as AIBN and dilauroyl peroxide (DLP) were also found to be ineffective in promoting the desired reaction (Table 1, entries 5 and 6), although we have recently found that similar reactions of fluoroalkylsulfonyl chlorides with electron-rich alkenes produced 1:1 adducts in high yields when using DLP as the radical initiator. [20] We were encouraged, however, to find that the use of Ir(ppy) 3 in place of the Ru catalysts led to a 43-44 % yield of addition product (Table 1, entries 7 and 8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[19] Also, not unexpectedly, simple thermally induced radical initiators, such as AIBN and dilauroyl peroxide (DLP) were also found to be ineffective in promoting the desired reaction (Table 1, entries 5 and 6), although we have recently found that similar reactions of fluoroalkylsulfonyl chlorides with electron-rich alkenes produced 1:1 adducts in high yields when using DLP as the radical initiator. [20] We were encouraged, however, to find that the use of Ir(ppy) 3 in place of the Ru catalysts led to a 43-44 % yield of addition product (Table 1, entries 7 and 8).…”
mentioning
confidence: 99%
“…However, when the substrate was substituted at the b position, as in 3 ae, yields were reduced significantly. In particular, excellent yields of 1:1 adducts were obtained from [a] All reactions were run with 0.3 mmol 2 a and 0.6 mmol CF 3 SO 2 Cl (1 a) in 2 mL solvent for overnight under visible light except entries 5 and 6, and yields were determined by 19 F NMR spectroscopy using PhCF 3 as the internal standard.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 The reaction of alkenes with CF 3 SO 2 Cl was carried out with Ru(phen) 3 Cl 2 as a catalyst and K 2 HPO 4 as a base in MeCN at room temperature to give the chlorotrifluoromethylation products in 54-99% yields. A variety of functional groups, such as N-protected amines, ethers, esters, amides, aldehydes, ketones, and quinolines could be tolerated.…”
Section: Electrophilic Cf 3 Reagentsmentioning
confidence: 99%
“…[12] Together with the advantages of a heterogeneous catalyst, we were delighted to see that it was possible to perform fluoroalkylations of various arenes with mpg-CN as a photoredox catalyst. Additionally, the reusability could be demonstrated with recycle experiments (see Figure S-1 in the Supporting Information).…”
mentioning
confidence: 99%